Crude Palm Oil Dikatalisis Enzim Lipase Amobil dengan Pengaruh Waktu Reaksi Menggunakan Packed Bed Reactor - Revi Indira Shafika; Martha Aznury; Indah Purnamasari (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Biodiesel is an alternative fuel based on renewable energy sources. Generally, chemical processes such as transesterification and esterification are used to produce biodiesel. The biodiesel process using lipase enzyme as a catalyst has the advantage of specific activity and easy separation due to catalyst heterogeneity. Considering the high price of the enzyme, immobilization in the matrix is carried out using cationic resin. The purpose of this study was to determine the effect of reaction time on the activation of immobilized lipase enzyme catalyst on biodiesel produced using packed bed reactor and to obtain optimum biodiesel product characteristics with variations of reaction time on viscosity, density, %yield, iodine number, saponification number, cetane number, biodiesel acid number, total glycerol, methyl ester content and flash point. This research obtained the highest %yield of 86.35%, density of 878 Kg/m3, viscosity of 4.39 cSt, cetane number 68.65, saponification of 144.58 mg KOH/g, acid number 0.47 mg KOH/g, iodine number 68.53 g I2/100g, total glycerol 0.19%, methyl ester 97.31% and flash point 101°C. From the ratio of oil and methanol 1:10, which meets the quality requirements of SNI 7182:2015.